(untitled) (Schermi. Storie e culture del cinema e dei media in Italia, 2019)
The article investigates two reports published at the end of the sixties about the corporate management of the Italian public service broadcaster: RAI. Both reports were born within the company itself. The first one has been commissioned by the top managers at RAI, while the second one comes from an association of internal programmers. Despite their different origin (top-down vs. bottom-up) and output, both reports ask for a renewed corporate organization, one that is capable of combining the socio-cultural mission of RAI with efficient economic management (that was neglected until that moment).